Penerapan Media Pembelajaran Interaktif Menggunakan Articulate Storyline untuk Meningkatkan Hasil Belajar Siswa dalam Mata Pelajaran Matematika Kelas X di Madrasah Aliyah Plus Ar Ruhama - Hermansyah, Maman; Lutfi, Ahmad Fajri (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The purpose of this study is to determine the influence of the application of articulate storyline interactive learning media on student learning outcomes in class X mathematics subjects at Madrasah Aliyah Plus Ar Ruhama. The method in this study is a quantitative method with a type of experimental research in the form of Pre-Experimental Design. The research design is One Group Pretest-Posttest Design. Sampling of this study uses a saturated sampling method, namely all members of the population are used as samples. This research was conducted on 12 students in class X. The data collection technique is carried out through the initial test and the final test. The data analysis technique was carried out through a t-test. The results of the research the average pretest score was 53.33, after the pretest was carried out then it was treated by using articulate storyline interactive learning media in mathematics subjects, after carrying out learning using articulate storyline interactive learning media there was an increase in learning outcomes which was seen from the posttest results where the average score was 76.67. Based on the results of the Paired sample t-test, it was concluded that the application of articulate storyline interactive learning media was influential in improving student learning outcomes in mathematics class X